2018
DOI: 10.1097/brs.0000000000001586
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for 30-Day Unplanned Readmissions After Elective Posterior Lumbar Fusion

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 39 publications
2
33
0
Order By: Relevance
“…When diagnostic testing after the failure of conservative treatment determines that there is a possibly surgical correctable problem such as an osteoporotic fracture or lumbar stenosis, there are multiple options. However, consideration must be given to the risk of the proposed procedures, type of anesthesia required, surgical time and estimated blood loss [12][13][14]. The experience of each surgeon with the specific minimally invasive procedure being performed and his/her adeptness at delivering local anesthesia in proper amounts and to the proper location is critical to minimizing the amount of overall sedation the patient receives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When diagnostic testing after the failure of conservative treatment determines that there is a possibly surgical correctable problem such as an osteoporotic fracture or lumbar stenosis, there are multiple options. However, consideration must be given to the risk of the proposed procedures, type of anesthesia required, surgical time and estimated blood loss [12][13][14]. The experience of each surgeon with the specific minimally invasive procedure being performed and his/her adeptness at delivering local anesthesia in proper amounts and to the proper location is critical to minimizing the amount of overall sedation the patient receives.…”
Section: Discussionmentioning
confidence: 99%
“…All of these factors affect the risk of peri-operative complications that may cause a longer hospital stay and increase the risk of readmission [10,13]. Several large studies have reported complications from fusion ranging from 5.1% to as much as 13% in elderly patients with multilevel surgery and instrumentation [13][14]. The majority of spinal surgery complications are mostly related to excessive blood loss, wound healing, cerebrospinal fluid leakage, hardware misplacement, pulmonary embolism, and thrombophlebitis [6][7]20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] The occurrence of postoperative complications following spine surgery has received much attention in the literature, as it has been shown to have serious impacts on patients' recoveries. [4][5][6][7] To facilitate the analysis of large populations for relatively rare complications, much research has turned to national databases, including the American College of Surgeons National Surgical Quality Improvement Program (NSQIP). NSQIP collects data from over 500 hospitals across the United States and has recently been extensively used in orthopedic research.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study utilizing NSQIP found that wound complications, pulmonary embolism, deep vein thrombosis, sepsis, and urinary tract infections (UTIs) are all associated with unplanned hospital readmission following PLF. 4 Using a smaller sample of 155 patients from a Food and Drug Administration-approved randomized trial regarding interventions for lumbar disc degeneration, it was discovered that patients who had adverse events related to their surgery reported higher pain scores and had decreased function at 2-year follow-up in comparison those who had no adverse events. 5 Furthermore, certain patient characteristics have been demonstrated to have an impact on patient recovery following elective PLF in both national data set studies as well as local cohort investigations.…”
Section: Introductionmentioning
confidence: 99%